Evaluación de la eficiencia de tres modelos de incubadora con diferentes flujos en el desarrollo larval de Osteoglossum bicirrhosum (arawana plateada) - Oliveros, Sergio Luis (2018)
The aim of this study was to evaluate the efficiency of three incubator models with different flow for the larval development of Osteoglossum bicirrhosum (silver arowana) from stage two to stage five. Sixty larvae were distributed in groups of 20 for each model of incubator: MI1: circular flow; MI2: upflow; MI3: no flow). Body diameter (DC), yolk sac diameter (DSV), swimming acquisition (AN) and mortality during 30 days of incubation were determined. The final DC for MI1 was 33.77 mm compared to 33.16 mm for MI2 and 19.92 mm for MI3. The initial DSV in MI1 of 12.03 mm decreased to 11.64 mm in MI2 and increased to 12.11 mm in MI3. The AN occurred in all larvae of MI1 and MI2, but only in 10% of MI3. Likewise, mortality was 1, 10 and 20 larvae for MI1, MI2 and MI3, respectively